Group Cohesiveness of Chelsea Indonesia Supporters Club (CISC) Bekasi Region in Building a Positive Community Image - Rafi Ardani; Fadli Muhammad Athalarik; Nasaruddin Siregar; Syahrul Hidayanto (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
Football is far more than a game; it is a cultural language that brings people together across nations and generations. In Indonesia, this passion for football extends beyond domestic leagues, where local supporters also form strong communities around international clubs. One of these is the Chelsea Indonesia Supporters Club (CISC) Bekasi Region, a collective of Chelsea FC fans who not only share admiration for the team but also nurture social bonds and a sense of belonging within their community. This paper offers a conceptual exploration of how cohesiveness among members of CISC Bekasi contributes to the creation of a positive community image. Building on ideas from scholars such as Mulyana (2016), Collins and Raven (in Arifuddin, 2016), and Muniz and O’Guinn (in Ratnawati & Lestari, 2018), the discussion focuses on the role of group communication in fostering solidarity and collective identity. Within the group, communication is not limited to exchanging information but also functions as a medium for emotional support, shared values, and moral responsibility. The argument put forward is that effective communication and social cohesion can transform a fan club into a respected social group that embodies unity and positive representation. The experience of CISC Bekasi illustrates how sports enthusiasm, when supported by strong interpersonal ties, can encourage inclusive participation and strengthen the public image of football supporter communities in Indonesia.